Independence day - Emmerich, Roland; Devlin, Dean.; Twentieth Century-Fox Film Corporation; Centropolis Entertainment (Firm).; Twentieth Century Fox Home Entertainment, Inc.; Viva Video (Beverly Hills, Calif. Twentieth Century Fox Home Entertainment; distributed in the Philippines by Viva Video, 2013)
Massive spaceships appear in Earth's skies and wonder turns to terror as the ships blast destructive beams of fire down on cities all over the planet. The world's only hope lies with a determined band of survivors.
Videodisc release of the 1996 motion picture.
Director of photography, Karl Walter Lindenlaub ; editor, David Brenner ; music, David Arnold.
Will Smith, Bill Pullman, Jeff Goldblum, Mary McDonnell, Judd Hirsch, Margaret Colin, Randy Quaid, Robert Loggia, James Rebhorn, Harvey Fierstein.
VCD.
Keywords: Human-alien encounters -- Drama; Space warfare -- Drama